التشكيل البصري في ديوان "صمتك وحناجري" لنسيبة عطاء الله - سعود, سهيلة; فرحات, هيبة (جامعة الوادي - university of Eloued, 2023)
يعتبر التشكيل البصري وليد الحداثة والإنفتاح الشعري المحدث، وهو كل ما يمنحه النص للرؤية سواء أكانت على مستوي البصر أو على مستوى البصيرة، وتتعدد تسمياته من القصيدة البصرية، إلى الشعر المجسد، والشعر الحرفي، قصيدة العلامات .ومن هنا يكتسب أحقية وصفه بالبصري، ولا يمكن إدراكه الا عن طريق البصر أو الرؤية، وهذا ما ينتج جمالية شكلية تبرز خلاص البياض والسواد، وقد اضهرت الشاعرة نسيبة عطاء الله في ديوانها "صمتك وحناجري "عديد المظاهر للتشكيل البصري منها بنية الغلاف، وحركة الأسطر الشعرية بشكل واضح في قصائدها، اللغة العامية والأبجدية التي تحاول انتخلق شي جديد من خلال توضيفها لهذا المضهر، وايضا علامات الترقيم التي تتمثل في (الاستفهام؟،والتعجب!،والنقطة.، والفاصلة،، ...الخ، وإزدواجية البياض والسواد التي منحت للشاعرة التعبير عن مكنونات الذات الداخلية. Visual formatting is the product of modernity and innovative poetic openness, and it is everything that the text provides for vision, whether at the level of sight or insight. Its labels vary from visual poetry to embodied poetry, calligram, and sign poem. Hence, it rightfully earns its description as visual, and it cannot be perceived except through sight or vision. This produces an aesthetic of form that highlights the contrast between white and black. The poet Nesiba Ataa Allah displayed many manifestations of visual formatting in her collection "Your Silence and My Throat," including the structure of the cover, the movement of poetic lines in her poems, the use of colloquial language and alphabet to create something new through this appearance, punctuation marks such as "?" and "!", and the duality of white and black that allowed the poet to express her inner self..
أدب حديث ومعاصر
Keywords: - التشكيل البصري - ديوان - صمتك وحناجري- لنسيبة عطاء الله; Visual composition - Diwan - Your silence and my throat - by Nusseibeh Atallah.